2005
DOI: 10.1021/pr050046x
|View full text |Cite
|
Sign up to set email alerts
|

Direct Tandem Mass Spectrometry Reveals Limitations in Protein Profiling Experiments for Plasma Biomarker Discovery

Abstract: The low molecular weight plasma proteome and its biological relevance are not well defined; therefore, experiments were conducted to directly sequence and identify peptides observed in plasma and serum protein profiles. Protein fractionation, matrix-assisted laser desorption ionization mass spectrometry (MALDI-MS) profiling, and liquid-chromatography coupled to MALDI tandem mass spectrometry (MS/MS) sequencing were used to analyze the low molecular weight proteome of heparinized plasma. Four fractionation tech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
200
3

Year Published

2006
2006
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 201 publications
(220 citation statements)
references
References 81 publications
(123 reference statements)
17
200
3
Order By: Relevance
“…One of these ladders is derived from fibrinogen alpha as shown in Table 2. This ladder is similar to non-phosphorylated endogenous peptide ladder described previously [2,31]. Another ladder of phosphopeptides coming from alpha-2-HS-glycoprotein was also detected.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…One of these ladders is derived from fibrinogen alpha as shown in Table 2. This ladder is similar to non-phosphorylated endogenous peptide ladder described previously [2,31]. Another ladder of phosphopeptides coming from alpha-2-HS-glycoprotein was also detected.…”
Section: Discussionsupporting
confidence: 84%
“…Due to the presence of active exopeptidases in serum, non-phosphorylated endogenous peptide ladders were observed in peptidomic studies [2,31]. In this study, several phosphopeptide ladders were also observed.…”
Section: Discussionmentioning
confidence: 53%
“…This has been reported previously and may be due to the presence of degradation products of the most abundant serum proteins. 31,32 Protein A/G depletion did not impact sequence coverage of IgG, likely due to saturation of the column by the abundant immunoglobulins. Similarly, C3 and C8 bead-based fractionation did not significantly change the hydrophobicity distribution of the identified proteins relative to unfractionated serum, nor did fractionation by WCX beads impact the distribution of isoelectric points (Table 4).…”
Section: Lc-ms/ms On a Linear Ion Trap: (3) The Variability Of Peptidmentioning
confidence: 97%
“…Recently, over 250 peptides up to a mass of 5500 d were identified as derivatives of plasma proteins released by plasmin, thrombin or complement proteases [89]. In almost all cases there were peptide isoforms lacking the predicted C-terminal Arg or Lys residues and it was considered to be evidence of hydrolysis by CPN [89].…”
Section: Hydrolysis Of Biologically Relevant Peptides In Vivomentioning
confidence: 99%
“…Recently, over 250 peptides up to a mass of 5500 d were identified as derivatives of plasma proteins released by plasmin, thrombin or complement proteases [89]. In almost all cases there were peptide isoforms lacking the predicted C-terminal Arg or Lys residues and it was considered to be evidence of hydrolysis by CPN [89]. Whether this cleavage has physiological significance is unknown as the biological activities of these peptides have not been tested, but it should be taken into consideration when measuring peptide levels as biomarkers.…”
Section: Hydrolysis Of Biologically Relevant Peptides In Vivomentioning
confidence: 99%